EFEK PENGGUNAAN BETA BLOCKER TERHADAP KEJADIAN HIPOGLIKEMIA PADA LANSIA: NARRATIVE REVIEW - Adisaputra, Arya Dibyo; Susilawati, Ni Made; Fatkhiya, Musa Fitri; Gibran, Nabial Chiekal; Futihat, Chilyati Eky (Jurnal Buana Farma, 2025)
Elderly patients are considered a vulnerable population, as advanced age may exacerbate existing conditions or predispose individuals to adverse effects such as hypoglycemia. While hypoglycemia most frequently occurs in patients with diabetes who are treated with insulin or oral hypoglycemic agents, it may also develop in non-diabetic individuals under certain circumstances. The use of beta-blockers has been identified as one potential contributing factor to hypoglycemic events. This article aims to review the adverse effects of beta-blocker therapy in relation to hypoglycemia among older adults. A narrative review was conducted through electronic databases including PubMed, Google Scholar, and ScienceDirect. The inclusion criteria were studies published within the last 10 years involving older patients who experienced hypoglycemia while receiving beta-blocker therapy. The search yielded 38 articles, of which only 4 met the inclusion criteria. In conclusion, the use of β-blockers appears to be associated with an increased risk of severe hypoglycemia; however, evidence specifically addressing the geriatric population remains limited.